Evaluation and comparing rectum and bladder's clinical complications in pelvis radiotherapy in order to treat prostate cancer by using custom block and MLC for three- dimensional conformal radiotherapy - Sabzi, Sadegh; Bakhshandeh, Mohsen; Houshyari, Mohammad; Shakeri, Nezhat; Jabbary Arfaee, Ali (Archives of Advances in Biosciences, 2016)
Ionization radiation caused to incidence of complications in the exposed organs. In prostate radiotherapy, rectum and bladder have been radiated unwantedly and indicated some complications during and after treatment. The purpose of present study is to consider and to compare clinical complications of rectum and bladder in custom block and MLC for 3- D conformal radiotherapy, in order to determine if both treatments differ with respect to creating radiation protection, subsequently in the incidence of complications. In this respect, 72 patients with prostate cancer classified into two arms, above 60 years without the history of previous radiotherapy, hormone therapy and surgery, were selected randomly in October 2014. In one arm, patients were treated with block 3- D conformal radiotherapy, and in second arm with MLC outbound technique for 3- D radiotherapy. Rectal and bladder clinical complications were recorded before, during (at the end of 10 treatment sessions), 3 and 6 months after treatment then compared based on tables (RTOG/ LENT).Obtained results showed that patients had a significant difference in such complications as urinary frequency after 10 treatment sessions, 3 months after treatment (p<0.02 and p<0.04, respectively) Also, patients had a significant difference in regard to dysuria at the end of treatment (p<0.02). In both arms, patients had a significant difference in constipation after 30 sessions also at the end of treatment (p<0.02, p<0.02, respectively).In comparing different grades of complications based on RTOG/ LENT tables, it was not observed a significant difference between patients' complications in both arms.